Dada a função quadrática f(x)= 3x² - 4x + 1, determine
a) f(1)
b) f(2)
c) f(-2)
d) x de modo que f(x)= 1
Soluções para a tarefa
Respondido por
1
a) f(1) = 3 × 1² - 4 × 1 + 1 = 3 - 4 + 1 = 0
b) f(2) = 3 × 2² - 4 × 2 + 1 = 3 × 4 - 4 × 2 + 1 = 12 - 8 + 1 = 5
c) f(-2) = 3 × (-2)² - 4 × (-2) + 1 = 3 × 4 - 4 × 2 + 1 = 12 - 8 + 1 = 5
d) f(x) = 1 ⇔
⇔ 3x² - 4x + 1 = 1 ⇔
⇔ 3x² - 4x = 0 ⇔
⇔ x × (3x - 4) = 0 ⇔
⇔ x = 0 ∨ 3x - 4 = 0 ⇔
⇔ x = 0 ∨ 3x = 4 ⇔
⇔ x = 0 ∨ x = 4/3
x = { 0 ; 4/3 }
Perguntas interessantes
Português,
10 meses atrás
Saúde,
10 meses atrás
Matemática,
10 meses atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás
Geografia,
1 ano atrás